Influence of atypical pluviosity on phytoplankton assemblages in a stretch of a large sub-tropical river (Brazil) - Perbiche-Neves, Gilmar [UNESP]; Ferrareze, Mateus F. [UNESP]; Serafim-Junior, Moacyr; Shirata, Madalena T.; Lagos, Patricia E. D. (Versita, 2011)
This study aimed to evaluate the influence of alterations in pluviosity and ecological variables on microphytoplankton (> 20 mu m) structure (composition, richness, diversity, and abundance) and its biomass (chlorophyll-a), comparing different regions in a stretch of the low Igua double dagger u River and in some tributaries. Phytoplankton was sampled in 10 stations (5 in Igua double dagger u River and 5 in tributaries) during a dry period (April/2004) and an atypical rainy period (June/2004). The conductivity showed significant difference among the sampling points. Temperature, dissolved oxygen, pH, silicate, and nitrate showed significant differences between the dry and wet periods. Phytoplankton was composed of 149 taxa, and the most representative class was Chlorophyceae (71 taxa), followed by Bacillariophyceae (35 taxa), and Cyanophyceae (25 taxa). During the rainy period, stations of Igua double dagger u River showed higher taxa number and total density compared to the tributaries, but the values were similar in the dry period. Tributaries presented higher diversity and equitability in both periods. Except by two stations in Igua double dagger u River, the higher taxa number, densities and biomass occurred in the dry period, associated to low levels of suspended matter. The canonical correspondence analysis indicated the dominance of Bacillariophyceae and Chrysophyceae in the rainy period related to nitrate and suspended matter. Two other groups were observed in the dry period: one formed by Cyanophyceae, Dinophyceae, and Rhodophyceae, related to temperature and nitrite and other by Euglenophyceae and Chlorophyceae related to total phosphorus and silicate. The groups suggest adequate conditions of the physical, chemical and climatic factors to the establishment of the algae classes. Phytoplanktonic assemblages responded quickly to the environmental regional variations under strong influence of pluviosity, while in the dry period, homogeneity among stations and environmental variables was observed. The importance of climatic events is relevant in ecological studies in a temporal scale.
Keywords: dry and rainy periods; phytoplankton; potamoplankton; tributaries; Iguacu River